Cross−Trial Query System for Cancer Clinical Trials - Calinescu, R; Harris, S; Gibbons, J; Davies, J (2007)
Data sharing represents one of the key objectives and major challenges of today's cancer research. CancerGrid, a consortium of clinicians, cancer researchers, computational biologists and software engineers from leading UK institutions, is developing open-standards cancer informatics addressing this challenge. The CancerGrid solution involves the representation of a widely accepted clinical trials model in controlled vocabulary and common data elements (CDEs) as the enabling factor for cancer data sharing. This paper describes a cancer data query system that supports data sharing across CancerGrid-compliant clinical trial boundaries. The formal specification of the query system allows the model-driven development of a flexible, web-based interface that cancer researchers with limited IT experience can use to identify and query common data across multiple clinical trials.